Implementasi Pengabdian Masyarakat Terhadap Pengoptimalan Fungsi Kolam Lele Melalui Pembuatan Instalasi Aquaponic Bagi Kelompok Disabilitas Di Desa Gledeg, Karanganom, Klaten - Al Hafiiz Abdika Muhammad; Deva Nur Putri Altiara; Ganung Nalendra; Hanijaya Intan Pratiwi; Hasan Al Bana; Hilmy Yahya; Ilma Aurarisa; Irfan Tri Laksono Hadi; Mitha Sinayang Wahyu Candini; Silvina Dyah Ramadhanty; Sudibya (KREASI : Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2022)
Abstract Community Services with a work program for making aquaponic installations for disabled groups farmers in Gledeg Village aims to maximize the potential of existing ponds through the creation of aquaponics integrated with plants above the pond so to provide more income for cultivators. The idea of using aquaponics is one solution in maintaining the cleanliness of the catfish pond because the dirty water at the bottom of the pond is used to water plants as well as a filter to keep the water clean. The impact of this activity is expected to become new knowledge for the Gledeg Village community in utilizing the existing land to maximize its potential, through the display of existing installations it can easily be an example in making other aquaponics installations. Keywords: Aquaponic, Catfish, Plant